Analisis Film Animasi dalam Game Valorant: Tinjauan Pustaka sistematis - Aisyah, Inas Hana (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2023)
This article aims to detail the role and impact of animated films in games, specifically in the game Valorant, with the aim of providing valuable insights for players, developers and practitioners in the industry. Through a systematic literature review approach, this research reveals that cinematic elements have a central role in creating a compelling and powerful game experience. The careful integration of cinematic elements and gameplay in modern FPS games, such as Valorant, has achieved a high level of aesthetic and visually appealing quality, significantly impacting the player experience. The implications of these findings not only enrich the literature studies in the field of animation and games, but also provide valuable insights for game developers in improving the visual and narrative aspects of their games. Furthermore, a deeper understanding of the correlation between animated movies and games may pave the way for the development of comprehensive and engaging FPS games in the future.